2019
DOI: 10.1093/mnras/stz609
|View full text |Cite
|
Sign up to set email alerts
|

New hot subdwarf variables from the EC survey

Abstract: We present new results for hot subdwarf stars from the Edinburgh-Cape (EC) blue object survey. EC 03089-6421, an sdO star recently discovered to be a very rapid pulsator with periods near 31.1 and 34.2 s (29.2 and 32.1 mHz), is shown to have an even faster pulsation near 26.6 s (37.6 mHz) although all pulsations are variable in amplitude and effectively disappear in one of our runs. Five stars are discovered to be of the rapidly-pulsating (sdBV r

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 76 publications
(78 reference statements)
1
13
0
Order By: Relevance
“…In addition, several recent studies reported the discovery of individual subdwarfs (Hillwig et al 2017;Kupfer et al 2017aKupfer et al ,b, 2020Kupfer et al , 2022Holdsworth et al 2017;Ratzloff et al 2019Ratzloff et al , 2020Kilkenny et al 2019;Bell et al 2019;Hogg et al 2020;Silvotti et al 2021;Pelisoli et al 2021;Vos et al 2021;Dorsch et al 2022;Silvotti et al 2022;Werner et al 2022a,b), all of which are included in our compilation.…”
Section: Input Datamentioning
confidence: 96%
“…In addition, several recent studies reported the discovery of individual subdwarfs (Hillwig et al 2017;Kupfer et al 2017aKupfer et al ,b, 2020Kupfer et al , 2022Holdsworth et al 2017;Ratzloff et al 2019Ratzloff et al , 2020Kilkenny et al 2019;Bell et al 2019;Hogg et al 2020;Silvotti et al 2021;Pelisoli et al 2021;Vos et al 2021;Dorsch et al 2022;Silvotti et al 2022;Werner et al 2022a,b), all of which are included in our compilation.…”
Section: Input Datamentioning
confidence: 96%
“…In addition, several recent studies reported the discovery of individual subdwarfs (Hillwig et al 2017;Kupfer et al 2017aKupfer et al ,b, 2020Kupfer et al , 2022Holdsworth et al 2017;Ratzloff et al 2019;Kilkenny et al 2019;Bell et al 2019;Hogg et al 2020;Ratzloff et al 2020;Silvotti et al 2021;Pelisoli et al 2021;Vos et al 2021;Dorsch et al 2022;Silvotti et al 2022;Werner et al 2022a,b), all of which are included in our compilation.…”
Section: Input Datamentioning
confidence: 96%
“…Asteroseismology of the much rarer sdOV stars is still developing (Van Grootel et al 2019). Kilkenny et al (2017) and Kilkenny et al (2019) discovered an sdOV star, EC 03089-6421, with T eff = 52 000 K and M ∼ 0.1 M⊙, pulsating with very short periods of 27 s, 31 s, and 34 s. The pulsations in this star are potentially driven by the ǫ-mechanism and it may be a progenitor of an ELM white dwarf. Finding pulsations driven by the ǫ-mechanism is a long-standing goal, with previous claims or suggestions that have not been confirmed.…”
Section: V366 Aqr Starsmentioning
confidence: 98%